2016
DOI: 10.1093/jee/tow086
|View full text |Cite
|
Sign up to set email alerts
|

Pest Control and Pollination Cost–Benefit Analysis of Hedgerow Restoration in a Simplified Agricultural Landscape

Abstract: Field edge habitat in homogeneous agricultural landscapes can serve multiple purposes including enhanced biodiversity, water quality protection, and habitat for beneficial insects, such as native bees and natural enemies. Despite this ecosystem service value, adoption of field border plantings, such as hedgerows, on large-scale mono-cropped farms is minimal. With profits primarily driving agricultural production, a major challenge affecting hedgerow plantings is linked to establishment costs and the lack of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 42 publications
3
107
0
1
Order By: Relevance
“…In one case, pollination services were measured 10 years post-establishment, but data from the interim was not presented (Morandin et al 2016). Time to pay off PR cost can take three or four years for cultivated highbush blueberry with and without a subsidy, respectively (Blaauw and Isaacs 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In one case, pollination services were measured 10 years post-establishment, but data from the interim was not presented (Morandin et al 2016). Time to pay off PR cost can take three or four years for cultivated highbush blueberry with and without a subsidy, respectively (Blaauw and Isaacs 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, with a cost-benefit analysis, Morandin, Long, and Kremen (2016) demonstrated that increased pollination (and pest control) services render hedgerows economically viable for growers. A number of studies in different crops, such as coffee (Klein, Steffan-Dewenter, and Tscharntke 2003), pumpkins (Hoehn et al 2008), and apples (Blitzer et al 2016), have documented a positive relationship between pollinator diversity and crop yield.…”
Section: Local Effectsmentioning
confidence: 99%
“…Tomato crops with hedgerows required less input of insecticides than those without them. Considering only the reduction in insecticide treatments, and a cost of $4,000 for hedgerow installation and establishment (Long and Anderson 2010), profit was realized after 16 years (Morandin et al 2016; fig. 1).…”
Section: Improved Pest Control and Pollinationmentioning
confidence: 99%
“…Hedgerows also exported native bees into adjacent tomato crops, where sentinel canola (potted plants used to assess pollination effects) had greater bee abundance than sentinel canola plants adjacent to conventionally managed field edges. Hedgerow profit from pollination enhancement in canola and enhanced biocontrol of insect pests was realized after 7 years (Morandin et al 2016; fig. 1).…”
Section: Improved Pest Control and Pollinationmentioning
confidence: 99%
See 1 more Smart Citation